LCR based quick detection of hotspot G1896A mutation in patients with different spectrum of hepatitis B - Abdul Malik; Fahad Aldakheel; Syed Rabbani; Meshal Alshehri; Anis Ahmad Chaudhary; Musaed Alkholief; Aws Alshamsan (Elsevier, 2021)
G1896A switch is one of the hotspots in subjects affected with hepatitis B. This hotspot mutation is observed in all the different spectrum of hepatitis B, and it has a very dangerous and a long lasting effect. The major purpose of the study was to screen G1986A mutations at a large scale and also to establish ligase chain reaction as a mutation testing tool. Polymerase chain reaction (PCR) and Nucleotide Sequencing was done to identify the G1896A mutation in the precore region of the genome. All the 331 HBV positive patients were screened. Almost 29% (24/82) of the cases remarkably had the presence of G1896A mutation confirmed by LCR and direct sequencing.The precore G1896A mutation is responsible for one third of the patients suffering from precore stop codon mutation. It clearly exhibits that LCR is 100% in sync with direct sequencing and is extremely reliable and the results are highly reproducible.